Photo-induced shrinking of aqueous glycine aerosol droplets - S. Ishizuka; S. Ishizuka; S. Ishizuka; O. Reich; G. David; R. Signorell (Atmospheric Chemistry and Physics, 2023)
Due to their small size, micrometer- and submicrometer-sized solution droplets can respond differently to physical and chemical processes compared with extended bulk material. Using optically trapped micrometer-sized aqueous glycine droplets, we demonstrate a photo-induced degradation of glycine upon irradiation with visible light, even though molecular glycine does not absorb light in the near-UV–vis range to any significant extent. This reaction is observed as photo-induced shrinking of the droplet, which we characterize by analyzing the elastic light scattering and the Raman spectrum of the droplet over the course of the reaction. We find the volume to shrink with a constant rate over the major part of the shrinking process. This indicates the presence of a rate limiting photo-catalyst, which we attribute to mesoscopic glycine clusters in the droplet solution. Our findings relate to previous reports about enhanced absorption and fluorescence rates of amino acid solutions. However, to the best of our knowledge, this is the first experimental evidence of a photochemical pathway facilitated by mesoscopic clusters. Light interaction with such mesoscopic photoactive molecular aggregates might be more important for aerosol photochemistry than previously anticipated.